2004
DOI: 10.1046/j.1365-3180.2003.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resistance to Orobanche crenata in species of Cicer

Abstract: Crenate broomrape (Orobanche crenata) is a major constraint for legume cultivation in Mediterranean agriculture. Field trials, pot and in vitro experiments demonstrated that resistance to O. crenata is present in chickpea and wild species of Cicer. The resistance is the result of the combination of several mechanisms, including low induction of parasite seed germination and in some accessions, either a darkening at the infection site on the host root that prevents establishment, or a reduced development of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…crenata, reduced orobanche seed germination percentage appears to be a key in the resistance mechanism in some Cicer accessions. Most studies on legume resistance to broomrape concluded that resistance is correlated with low stimulatory activity by root exudates of the host plant (Rubiales et al, 2003b;2004;Abbes et al, 2007b;. In contrast, several other studies showed that resistant accessions presented the same orobanche seeds germination percentage or even greater than that observed on a sensitive accession (Ter Borg et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…crenata, reduced orobanche seed germination percentage appears to be a key in the resistance mechanism in some Cicer accessions. Most studies on legume resistance to broomrape concluded that resistance is correlated with low stimulatory activity by root exudates of the host plant (Rubiales et al, 2003b;2004;Abbes et al, 2007b;. In contrast, several other studies showed that resistant accessions presented the same orobanche seeds germination percentage or even greater than that observed on a sensitive accession (Ter Borg et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, chickpea displays a lack of adaptive diversity for a range of biotic and abiotic stresses. Unlike cultivated chickpea, wild Cicer species possess useful variation for morphological traits (Robertson et al, 1995), protein content , and genetic sources for resistance to both biotic (Di Vito et al, 1996;Collard et al, 2001;Ansari et al, 2004;Rubiales et al, 2004) and abiotic stresses Croser et al, 2003;Toker, 2005;Toker et al, 2007ab;Canci et al, 2009 Vito et al, 1996;Collard et al, 2001;Croser et al, 2003;Ansari et al, 2004;Sharma et al, 2005;Sillero et al, 2012). By far the most pressing issue relating to chickpea genetic resources is the urgent need to collect and characterize annual wild relatives, particularly those that are readily crossable with domestic chickpea (Ben-David et al, 2010).…”
Section: Crop Chickpea (Cicer Arietinum L)mentioning
confidence: 99%
“…25 Genetic maps were also used to identify and locate QTL associated with resistance to O. crenata, another parasitic weed that seriously attacks legume crops as well as wild legume species. [26][27][28] Two QTL were detected in peas 26,27 and three QTL were found in faba bean. 28 Orobanche cumana is specialized and parasitizes sunflower.…”
Section: Resultsmentioning
confidence: 99%